TanDEM-X Mission and DEM Accuracy - Gonzalez, Jaime Hueso; Bachmann, Markus; Böer, Johannes; Fiedler, Hauke; Krieger, Gerhard; Zink, Manfred (Wave Propagation in Communication, Microwaves Systems and Navigation (WFMN), 2009)
TanDEM-X (TerraSAR-X Add-on for Digital Elevation Measurements) is currently implemented as a national Earth observation mission by the German Aerospace (DLR) and EADS Astrium GmbH. This first bistatic satellite synthetic aperture radar (SAR) mission opens a new era in spaceborne radar remote sensing. The tandem configuration is formed by flying TanDEM-X and TerraSAR-X in a closely controlled helix formation. The primary mission goal is the derivation of a high-precision global Digital Elevation Model (DEM) with 12 m resolution, 10 m absolute height accuracy and 2 m relative height accuracy. This paper provides an overview of the mission with main focus on the data acquisition concept for the interferometric radar data and the derivation of the specified accurate global DEM.
DLR Import::2019-04-03